Studying the physical features of different surfaces using atomic force microscopy methods - Useinov Б.М.; Samutkin А.Г.; Samutkin Я.Р.; Solodovnik А.А.; Kassimova С.А. (Recent Contributions to Physics, 2025)
Scanning probe microscopes are an advanced means of obtaining information about the structure of a surface in dimensional regions where optical microscopes are already powerless. The purpose of the work is to study the physical characteristics of the surfaces of various materials using a scanning probe microscope. Hypothesis: it is possible to obtain information about the physical structure of the surface of a material at the micro- and nanolevel, and the existence of a relationship between the physical characteristics of the surface and the contact angle. Methods used: obtaining images of surfaces using atomic force microscopy methods on a scanning probe microscope, software processing and analysis of images in the Nova Px program The results of the study are presented in the form of information on surface roughness and the properties of interaction with water. Analysis of the contact angle can make it possible to judge the state of the surface and its roughness in the absence of expensive equipment.